2022
DOI: 10.1108/aaouj-08-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Applying the UTAUT2 to predict the acceptance of blended learning by university students

Abstract: PurposeThe study applied the Unified Theory of Technology Acceptance and Use Theory 2 (UTAUT2) to predict blended learning acceptance by students in universities in Zimbabwe. Blended learning is a heterogeneous mode of teaching and learning that combines face-to-face (F2F) and online modes. Owing to advances in technology, and recently, the advent of pandemics, such as COVID-19, the need for multimodal teaching approaches, such as blended learning, to enhance access to education in universities has become very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 51 publications
10
28
0
1
Order By: Relevance
“…Hedonic Motivation (HM) is defined as the fun or pleasure derived from the use of technology and, according to previous works, it can be stated that this is a very influential factor concerning the consumer's intention to use the technology (Alalwan et al, 2018; Baabdullah et al, 2019; Brown & Venkatesh, 2005; Hamari & Koivisto, 2015). This is also corroborated in a current work (Rudhumbu, 2022). Based on the above, the following hypothesis can be formulated:Hypothesis Hedonic motivation positively affects the consumer's intention to use the Zara app .…”
Section: Theorical Frameworksupporting
confidence: 91%
See 3 more Smart Citations
“…Hedonic Motivation (HM) is defined as the fun or pleasure derived from the use of technology and, according to previous works, it can be stated that this is a very influential factor concerning the consumer's intention to use the technology (Alalwan et al, 2018; Baabdullah et al, 2019; Brown & Venkatesh, 2005; Hamari & Koivisto, 2015). This is also corroborated in a current work (Rudhumbu, 2022). Based on the above, the following hypothesis can be formulated:Hypothesis Hedonic motivation positively affects the consumer's intention to use the Zara app .…”
Section: Theorical Frameworksupporting
confidence: 91%
“…In 2012 Venkatesh et al demonstrated through UTAUT2 that this variable has a notable influence with respect to the intention to use (Cabrera‐Sánchez & Villarejo‐Ramos, 2018). Other studies have also corroborated this positive effect (Agarwal & Sahu, 2022; Rudhumbu, 2022).…”
Section: Theorical Frameworksupporting
confidence: 53%
See 2 more Smart Citations
“…Various studies in different contexts have been conducted by using UTAUT to investigate the factors influencing emerging technologies such a mobile technology, artificial intelligence, wearable technology and smart technology (Aytekin et al, 2022;Lin et al, 2022;Mishra et al, 2022). The justification of using the first version of UTAUT rather than the extended ones such as UTAUT 2 and 3 was the variance of prediction of the first version was the highest 70% (Gunasinghe and Nanayakkara, 2021) where the other versions between 62 to 66% (Rudhumbu, 2022;Tetteh et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%